The basement membrane zone and dermal extracellular matrix in erosive lichen planus of the vulva: an immunohistochemical study demonstrating altered expression of hemidesmosome components and anchoring fibrils. - Cooper, S; Prenter, A; Allen, J; Dean, D; Wojnarowska, F (2005)
Histopathology demonstrates disruption of the basal layer of the epidermis in lichen planus (LP) and altered expression of basement membrane zone (BMZ) components occurs in cutaneous and oral LP. This is the first study in erosive LP of the vulva to investigate the expression of components of the BMZ and extracellular matrix by indirect immunofluorescence. Six biopsies from lesional vulval erosive LP were compared with two biopsies from normal vulva and five biopsies from normal skin. In erosive vulval LP there was widespread disruption of several BMZ components compared to normal skin. The hemidesmosome antigens were disrupted and attenuated, or absent. Expression of lamina lucida proteins and anchoring filaments also showed some alteration. Lamina densa components were altered and in particular there was very marked thickening, streaking and fragmentation of the anchoring fibrils. Some dermal extracellular matrix proteins were increased. This study has demonstrated widespread damage to the BMZ in erosive LP of the vulva, in particular the hemidesmosomes (alpha6beta4 integrin, BP230, BP180) and anchoring fibrils (collagen VII). This suggests an alteration in antigenic expression in the BMZ that may lead to exposure of epitopes and thus make these proteins vulnerable to attack by autoantibodies.